Dimensi Kualitas Pelayanan Islami dan Hubungannya Terhadap Kepuasan Pasien di Rumah Sakit - Hanun, Hafida Zahara; Jati, Sutopo Patria; Arso, Septo Pawelas (Dinasti Research, 2025)
In an effort to provide optimal service, hospitals must consider quality standards involving medical and non-medical aspects. Indonesia, the world's largest Muslim-majority country, faces demand to integrate Islamic values into health care. Although the number of Islamic hospitals continues to grow, there are still challenges in understanding and implementing the quality of Islamic services consistently. This study aims to determine the dimensions of Islamic service quality and its relationship with patient satisfaction in hospitals. This study used the scoping review method with reference to PRISMA guidelines. Article searches were conducted on Google Scholar with the keywords